Wellness in the Face of Frailty Among Older Adults in First Nations Communities. (October 2022) - Slater, Morgan; Bruser, Gabrielle; Sutherland, Roseanne; Andrew, Melissa K.; Warry, Wayne; Jacklin, Kristen M.; Walker, Jennifer D.
Objectives: First Nations people report high levels of wellness despite high rates of chronic illness. Our goal was to understand the factors associated with wellness among First Nations adults in Ontario who were considered frail. Methods: Using the First Nations Regional Health Survey, we created a profile of First Nations adults (aged 45+) who were categorized as "frail" (weighted sample size = 8121). We used multivariate logistic regression to determine associations between wellness (as measured by self-reported physical, emotional, mental, and spiritual balance) and determinants of health. Results: Rates of reported wellness were high among those who were frail, ranging from 56.7% reporting physical balance to 71.6% reporting mental balance. Three key elements were associated with wellness: the availability of resources, individual lifestyle factors, and cultural connection and identity. Discussion: Our findings provide a profile of strength and wellness among older First Nations adults living with frailty.